Kierkegaard and Nietzsche - Kellenberger, J. author. aut Link
IX, 150 p.
Keywords: This book examines the thinking of two nineteenth-century existentialist thinkers, Soren Kierkegaard and Friedrich Nietzsche. Its focus is on the radically different ways they envisioned a joyful acceptance of life - a concern they shared. For Kierkegaard, in Fear and Trembling, joyful acceptance flows from the certitude of faith. For Nietzsche, in Thus Spoke Zarathustra, joyful acceptance is an acceptance of the eternal recurrence of life, and is ultimately a matter of will. This book explores the relationship between these opposed visions.